Assessing impacts of Common Agricultural Policy changes on regional land use patterns with a decision support system - Borges, P. J.; Fragoso, R.; Garcia-Gonzalo, J.; Borges, J. G.; Marques, S.; Lucas, M. R. (Forest Policy and Economics, 2010)
This paper discusses research aiming at assessing Common Agricultural Policy impacts on agriculture and forestry. For this purpose an approach is developed that includes a linear programming model to estimate the Positive Mathematical Programming production cost function coefﬁcients of current agricultural– forestry activities. It further includes a heuristic — simulated annealing — to generate solutions for each policy scenario. This model base approach is integrated within a decision support system (DSS) for testing purposes. The DSS further encompasses a relational database that stores agricultural–forestry technical and economic data and a geographic information system that stores topological data of regional farm-type land units. The DSS Graphical User Interface provides tabular and geographical reporting capabilities. Results are discussed for an application to the Alentejo region in Southern Portugal. Results demonstrate the usefulness and relevance of the proposed approach to assess the impact of changes in prices and in agricultural policy on land use patterns and on forestry
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Agricultural policy; decision support system; Land use pattern; mathematical programming; Simulation